Why use case specifications are hard to use in generating prototypes?. Issue 6 (1st December 2019) - Oran, Ana Carolina; Valentim, Natasha; Santos, Gleison; Conte, Tayana
Abstract : Requirements communication is essential in software development projects since customer needs must be communicated to the development team clearly and effectively. Although the use case (UC) specifications are used to communicate requirements in detail, developers do not always follow them. This study presents an empirical study carried out to understand the reasons why developers do not follow UC specifications and their difficulties using UC specifications in generating prototypes. Results show that the four reasons why developers fail to follow UC specifications are the existence of specification errors, ambiguous information, lack of detailed specification, or incomplete information, and due to improvement suggestions. Also, the specification defects types that impacted prototypes creation the most were an omission, ambiguity, and incorrect fact. The authors noted that 6 out of 25 (24%) defects in the UC specifications caused discrepancies in prototypes, 12 (48%) were corrected during the prototypes creation, and 7 (28%) were not propagated to the prototypes.